School-level predictors for the use of ICT in schools and students’ CIL in international comparison - Julia Gerick; Birgit Eickelmann; Wilfried Bos (Large-scale Assessments in Education, 2017)
Abstract The increasing relevance of information and communication technologies (ICT) and society’s transition towards an information or knowledge society have led to the emergence of new challenges for schools and school systems. Thus, the need for students to develop new forms of skills like digital literacy or computer and information literacy (CIL) is constantly gaining in importance. In the IEA’s (International Association for the Evaluation of Educational Achievement) ICILS 2013 (International Computer and Information Literacy Study), the aforementioned competencies were investigated—along with CIL learning contexts and outcomes (such as school-level factors in different education systems)—for the first time for secondary schools by applying computer-based student tests. The research presented in this paper focuses on the school-level factors that support or hinder the use of ICT by teaching staff and students’ CIL, drawing in the process on information obtained through school and teacher questionnaires. A multilevel approach was chosen for this research, drawing on representative data from four of the countries which participated in ICILS 2013, namely Australia, Germany, Norway and the Czech Republic. The results show that the relevance of school-level determinants for the use of ICT by teaching staff in schools differs between education systems. Only in Germany, for example, does pedagogical IT support seem to be crucial for the use of ICT in teaching. In the Czech Republic, the self-efficacy of teaching staff plays a key role, whereas in Australia, the participation of teaching staff in professional development activities can be identified as relevant for students’ acquisition of CIL. The results also show a statistically significant correlation between the teachers’ use of ICT in schools and students’ CIL for Germany, yet indicate no significant effects for Australia, Norway and the Czech Republic. In addition to these and the more specific findings for the considered countries, the international comparison presented in this paper reveals both strengths and developmental potential for the selected education systems.